Efek Ekstrak Air Kombinasi Daun Jati Belanda (Guazuma ulmifolia lamk.), Kemuning (Murraya paniculata (l.) Jack), Murbei (Morus alba l.), dan Rimpang Bangle (Zingiber purpureum roxb.) terhadap Derajat Perlemakan Hepar Tikus dengan Diet Tinggi Lemak - Krisnawati, Dyah Ika (Jurnal Kesehatan Islam : Islamic Health Journal, 2021)
Fatty liver is an accumulation of lipid drops exceeding 5% of the total amount of liver, which can increase the risk of nonalcoholic fatty liver disease (NAFLD). NAFLD is associated with dyslipidemia, which the treatments for both condition are in common. Jati Belanda leaves, Kemuning leaves, Murbei leaves and Bangle rhizome (JKMB) are often used alone or in combination to improve dyslipidemia, but their effect on the liver is unknown. This study used an experimental post test control group method where 25 rats were acclimatized for 2 weeks. After that, the rats were divided into 5 groups including KN : normal feed, KP : DTLM feed, D1 : DTLM+ JKMB extract dose 189 mg/200gbb, D2 : DTLM+ JKMB extract dose 378 mg/200gbb, D3 : DTLM+ JKMB extract dose 756 mg /200gbb and treated for 12 weeks. JKMB extract was obtained in a ratio of 8: 3: 3: 7. After that, the rats were sacrificed and the liver tissue was stained with Hematoxylin-Eosin staining. HE preparations were performed to calculate the percentage of liver fat at 400x magnification with 5 fields of view per slide. The results of the normality (0.200> 0.05) and homogeneity test (0.558> 0.05) were found to be normal. The ANOVA test was found to be significantly different (0.000< 0.05). The Post Hoc test found that the negative control was significantly different from the positive control (0.000 < 0.05). Positive control did not differ significantly with treatment doses D1 (0.094>0.05), D2 (0.186>0.05) and D3 (0.734>0.05). From the results of the research above, it can be concluded that the combination of extracts of Jati Belanda leaves, Kemuning leaves, Murbei leaves and Bangle rhizome extracts could not reduce the percentage of fatty liver.